Predisposition factors and control strategies of avian pathogenic Escherichia coli in laying hens - Waliaula, Paul K.; Kiarie, Elijah G.; Diarra, Moussa S. (Frontiers in Veterinary Science, 2024)
Shift in laying hens housing from conventional cage-based systems to alternatives has impacted their health and performance. Microorganisms colonize young chick in the early stages of their physiological and immune development. These colonizing microbes originate from parent and the environment. Escherichia coli is among the normal gut colonizing bacteria however, some E. coli strains known as avian pathogenic E. coli (APEC), cause local or systemic infections (colibacillosis) responsible of significant economic losses to the poultry industry. Potential APEC strains and other poultry gut microbiota are influenced by several factors such as housing system, and the use of feed additives (prebiotics, probiotics, symbiotic, among others). This review will discuss the status of pullets and layers immunity, gut health, and predisposing factors of colibacillosis. Dietary interventions and some colibacillosis mitigation strategies in pullets and laying hens are reviewed and discussed. With the development of sequencing technologies and the use of feed additives as alternatives to antibiotics, future studies need to understand some of the complex associations between the feed additives, the rearing environment, and their selective pressure on gut microbiota, including E. coli, and their impacts on immune development in pullets and hens.